Ecological civilization in the People Republic of China values, action, and future needs. ([Manila] Asian Development Bank, 2019)
Ecological civilization is being used by the Peoples Republic of China to provide a coherent conceptual framework for adjustments to development that meets 21st century challenges. This paper focuses on its significance as a concept, the challenges for applying it widely as a catalyst for reform and progress, and the strategic opportunities for its use in transformative change toward a new relationship between people and nature.
Keywords: Climatic changes -- China; Human ecology -- Cross-cultural studies; Electronic books